Does playing venue affect free testosterone concentrations in elite basketball players? - Matute-Llorente, A.; González-Agüero, A.; Gómez-Cabello, A.; Gómez-Bruton, A.; Morales, S.; Vicente-Rodriguez, G.; Casajús, J. A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The home advantage has been documented in some team sport competitions (Nevill and Holder, 1999). Pre-game increases in testosterone (T) levels have been reported with sports teams playing in their own home stadium, versus an opponent`s venue (Carré, 2009) which could be related to the concept of territoriality. However, we are unaware of any studies taking a dyadic approach to the assessment of playing venue and using basketball teams of similar rankings. Thus, this study examined the influence of playing venue on free T concentrations in elite basketball players of similar abilities. Method: 18 male athletes from 2 basketball teams were monitored during 2 competitive matches that were played against each other on a home and away basis. The teams were ranked first and second in the State championship during the monitoring period. Salivary free T was measured before and after each match and a session ratings of perceived exertion (RPE) was taken post-game. Results: Playing at home was accompanied by elevated pre-game free T concentrations compared to playing away (p < 0.05). The home teams also won their games. The T responses to competition were similarly elevated (% change from pre to post) when playing at home and away. No differences in session-RPE were noted across the playing venues. Discussion: Playing at one`s home venue resulted in elevated pre-match free T concentrations during competitive basketball games and these games were also won. The higher T concentrations at home might be related to the concept of territoriality and could be applicable to other team sports. Moreover, the territoriality and its association with dominance, aggressiveness and status emerges as a possible candidate to explain the perceived advantages of a sports team playing at their home venue, relative to playing at another venue (Archer, 2006). Interestingly, playing venue did not affect the free hormonal responses to competition, nor the perceived effort of athletes during these matches suggesting that perceived effort is independent of the playing venue and the corresponding outcomes of wins and losses.